Paleogeographic Methods For Studying the Development of the Nature of the Fergana Region in the Stratigraphic Sequence - Konstantin Andreevich Krakhmal (Zien Journals, 2023)
The article presents some results of studying the features of the paleogeographic development of the natural environment during the Anthropogenic periods in the stratigraphic sequence on the territory of the Tien Shan Mountain structures and the Fergana depression, the largest in Central Asia. As a result of local and regional constructions of stratigraphic schemes, a complex of monuments "Khanobad" was discovered in the eastern zone of the Chatkal ridge. The research results include an analysis of international trends in the development of modern trends and paradigms to determine the dynamics of geotectonic development, paleogeographic formation of landscape zonality, facies feature of sedimentation of the lithological substrate, biogeocenoses and biocommunities. Particular attention is paid to the definition of the evolution of ancient ecosystems, and humanity as an integral part of the biosphere as a whole. Some results of correlation comparisons of stratigraphic definitions of the cultural horizons of the early anthropogen Selungur, Sokh, Chashma and a newly discovered complex of sites in the eastern part of the Chatkal Range - Khanobad with the International Stratigraphic Scale are presented. A special place is given to the problems of detailing the chronostratigraphic stages, as well as paleogeographic reconstructions of the development of the natural environment, against which the formation of the most ancient cultures of mankind took place.
Keywords: Ferghana region; Khanobad; Selungur; Sokh